Wildlife-human relations and education in community-based marine tourism: a case study of coastal Oregon, U.S.A. - Fennell, Samuel R., author; Bright, Alan, advisor; Knight, David, committee member; Snodgrass, Jeffrey, committee member (Colorado State University. Libraries, 2023)
The tourism industry has witnessed an increased use of non-human animals, both within various attractions as well as in advertisements. This increased interaction and reliance can generate significant hazards which threaten the well-being of these non-human animals and require ongoing study. Animals in marine and community-based tourism destinations, in particular (e.g., coastal Oregon), are facing considerable pressures from tourism and climate change. In view of these concerns, this thesis represents a multi-species and multi-sited ethnography investigating the complexities around degrowth management, tourism policy, and education as a result of the COVID-19 pandemic within select Oregonian coastal and marine community-based tourism destinations. Utilizing a posthumanist critical lens, researchers gathered and thematically analyzed data gathered from local inhabitants on Oregon's coast. For efficiency and proficiency, the study employed the Vertical Integrated Projects (VIP) education model, allowing members to gain a hands-on and individualized educational experience. This study has significant relevance for the anthropology of tourism and environmental anthropology literature and broadens current understanding of marine and community-based tourism. Practical implications hold promise for the livelihoods of local Oregonian coastal animals, as well.
Keywords: community-based tourism; multi-species ethnography; vertical integrated projects (VIP) model; multi-sited ethnography; anthropology of tourism; posthumanism